THERAPEUTIC BIOLOGICAL ACTIVITIES OF Balanites aegyptiaca (L.) Delile: A REVIEW (Applied Biological Research, 2024)
Medicinal plants continue to be a crucial source of safe, less toxic, economical,  available, and reliable natural medicine supplies all over the world. Balanites  aegyptiaca Del. (Zygophyllaceae), commonly known as the "desert date", is a  thorny shrub or tree found in arid parts of Africa and South Asia. It has  traditionally been used to cure a variety of maladies such as wounds,  haemorrhoids, jaundice, syphilis, intestinal worm infection, malaria, dysentery,  constipation, diarrhoea, stomachaches, asthma, and fever. The fruits of B.  aegyptiaca are highly effective as antioxidants, anti-inflammatory, antibacterial,  antifungal, antiparasitic, antidiabetic, and anticancer. However, the safety and  effectiveness of B. aegyptiaca have not beencompletely studied in humans, so  additional well-planned clinical trials are required to corroborate preclinical  findings. The WHO has stressed on continued research on medical plants since  products derived from plants will continue to be in demand. Searches were  conducted on Google Scholar, Science Direct, Google.com, Wiley, PubMed,  Hindawi, Springer, and other relevant databases for research publications on B.  aegyptiaca. Duplicate publications including thesis papers, and reviews of B.  aegyptiaca were excluded This review presents a thorough overview of current  information on the therapeutic characteristics of B. aegyptiaca with a focus on  its biological activities. It briefly examines its traditional usage, taxonomy, and  biological evaluation.
Keywords: Antidiabetic; Balanites aegyptiaca; cancer; diabetes; plant extract